Draft Annual Plan 1989-90 Government of Gujarat - Planning Commission (Planning Commission, 1988)
The agricultural year 1987-88 for the third successive year was most unsatisfactory due to inadequate, irregular and uneven distribution of rainfall. Such a peculiar behaviour of monsoon has resulted into a considerable deterioration of crop condition for all kharif crops in the State except in the districts of South Gujarat region. Most of the areas of the State were affected by drought conditions for the third successive year. The insufficient rainfall has created serious problems of drinking water and fodder supply in many parts of the State. the State Government had declared scarcity in as many as 15369 villages out of 18114 villages covering 166 talukas in 17 districts out of 19 districts of the State.
Government of Gujarat, General Administration Department (Planning)